ORGANIZATIONAL TRANSFORMATION: MEMEDIASI PENGARUH INVESTASI TEKNOLOGI INFORMASI TERHADAP KINERJA ORGANISASI PADA PEMERINTAH DAERAH DI INDONESIA - Wiwik - Supratiwi; Dian Agustia (EKUITAS (Jurnal Ekonomi dan Keuangan), 2019)
The purpose of this research is to examine the role of organizational transformation in mediating the effect of Information Technology (IT) investments on organizational performance in local governments. This research is expected to assist local governments to implement IT effectively to improve their organizational performance. This research is designed as quantitative research. The unit of analysis of this study is the district/ city level. The research sample is 38 districts/ cities in East Java province using convenience samples due to the limitations of time, cost, and access to data collection. Data used are primary data collected through questionnaires to respondents from the determined Local Government Agencies in each sample district/ city. The data analysis of this study uses SEM-PLS because it can be used for the small number of samples and can predict complex models. Data processing using the Warp PLS 6.0 software application. This study uses the second-order construct model with reflective first-order and second-order. Variables are measured by using a 1-7 semantic differential scale. The theory used is the process theory with teleology typology. This study found that organizational transformation mediates partially the effect of IT investment on organizational performance in local governments. Future studies may add other mediation variables and use the different measurements for each latent variable, to test the consistency of the results of this study.